The Dictionary of Feminist Theory - Humm, Maggie (Edinburgh University Press, 2003)
The most comprehensive guide to the terminology and history of feminist theory available, this established and much admired dictionary provides succinct definitions of more than 600 terms, topics, movements and approaches as well as influential feminist thinkers, activists and critics within feminist theory.